The Effectiveness of Group Dialectical Behavior Therapy on Emotional Regulation and Rumination in Girls with Traumatic Experience - Ghavasi, Farideh; Akbarzadeh, Iman; Siran Hesari, Benyamin; Shams, Jamal; Mohammadian Ghezelghabr, Rasoul; Fatemizadeh, Mahdi (International Journal of Applied Behavioral Sciences, 2019)
Introduction: The aim of this study was to evaluate the efficacy of group dialectical behavior therapy on emotional regulation and rumination among female students with traumatic experiences. The traumatic experiences among teenagers and young females have various negative impacts on their future life. Methods: With reference to the Counseling Center of Education Ministry of Mashhad City. 24 female students with traumatic symptoms were selected in this quasi-experimental study to participate in this study. They were assigned randomly into control and experimental groups using the traumatic events questionnaire and the Structured Clinical Interview (SCID). In the pre-test, post-test and two-month follow-up, the difficulties in Emotion Regulation Scale of Gratz and Roemer (DERS) was conducted. The experimental participants spent 14 sessions of group dialectical behavior therapy. Results: The results demonstrated that there were a significant difference between mean scores of emotional regulation difficulties in girls with traumatic experiences who received group dialectical behavior therapy and the mean scores of emotional regulation difficulties in girls with traumatic experiences who did not receive the intervention (P<0.05). Conclusion: With the impact of dialectical behavior group therapy on the cognitive and emotional aspects of female participants with traumatic experiences, students were able to increase their emotional regulation and manage rumination. Declaration of Interest: None Key words: Dialectical behavior therapy, Rumination, Emotion regulation, Traumatic experiences.